PEMAKNAAN PERJUANGAN PEREMPUAN DI SOCIAL MEDIA (STUDI KASUS ARTIKEL “IBU, 10 TAHUN PENJARA, 10 MILYAR RUPIAH” DI DALAM BLOG WWW.ALANDAKARIZA.COM) - Pijar Suciati (Jurnal Vokasi Indonesia, 2015)
Abstract. This study, in general aimed to describe and know the meaning of the message womenstruggle by users of social media (Facebook and Twitter) to the blog article of Alanda Kariza. Thisstudy uses a critical paradigm of constructionism. The type is descriptive research using case studystrategy. Data collection techniques used is by interview (interview), with the selection ofinformants using purposive judgmental convenience. The conclusion that can be drawn from thisresearch is, in the end a meaning that appears in the mind of the reader to a blog written in socialmedia is influenced by many things, including the background of the blog readers. Whether it'sfamily background, educational background, ideology embraced, blog writing style and choice ofwords. Similarly, the meaning of which is trying to be revealed in this study, namely the meaning ofthe struggles of women was also influenced by the above factors. According to Stuart Hall, there arethree kinds of readings / interpretations of the text, namely (meaning dominant / hegemonic code,negotiated meaning / code, oppositional decoding / code). All three appeared in this study.Keywords: Social Media, Blogs, Meanings, Articles, Women Struggle